With crisis comes opportunity: Building ethical competencies in light of COVID-19. Issue 6 (17th August 2020) - Desai, Alisha; Lankford, C.; Schwartz, J.
ABSTRACT: The emergence of the coronavirus disease 2019 (COVID-19) pandemic has wide-ranging implications for the field of professional psychology. As clinical practice has rapidly adapted to ensure continuity of care, doctoral students have encountered unique opportunities for ethics-related competency development across practicum training settings. This article discusses the relevant American Psychological Association (APA) Ethics Code standards and additional ethical considerations facing trainees as they navigate their foundational clinical experiences and develop as professional psychologists in light of a pandemic.